2009
DOI: 10.1103/physreva.79.063836
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the quantum-classical transition in thermally seeded parametric down-conversion by intensity measurements

Abstract: Abstract. We address the pair of conjugated field modes obtained from parametricdownconversion as a convenient system to analyze the quantum-classical transition in the continuous variable regime. We explicitly evaluate intensity correlations, negativity and entanglement for the system in a thermal state and show that a hierarchy of nonclassicality thresholds naturally emerges in terms of thermal and downconversion photon number. We show that the transition from quantum to classical regime may be tuned by cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…In turn, the pair of field modes obtained from thermally seeded PDC is a convenient physical system to analyze the quantum-classical transition in the continuousvariable regime [20]. This scheme has already been investigated in ghost-imaging/diffraction experiments [18], where it was shown that both entanglement and intensity correlations may be tuned upon changing the intensities of the seeds [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the pair of field modes obtained from thermally seeded PDC is a convenient physical system to analyze the quantum-classical transition in the continuousvariable regime [20]. This scheme has already been investigated in ghost-imaging/diffraction experiments [18], where it was shown that both entanglement and intensity correlations may be tuned upon changing the intensities of the seeds [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…We note that entanglement and nonclassicality of twin beams generated by down-conversion seeded by thermal light have been analyzed in Refs. [46][47][48]. In this case, noise present in the incident thermal fields participates in the nonlinear process and generation of photon pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the experimental interest in the frame of quantum optics [28][29][30][31][32], in a recent paper [33] we have considered three different "quantumness" quantifiers applied to the study of quantum-classical transition in a thermal seeded parametric downconversion (PDC): a work that, a part its specific application, has a more general interest since it presents an idea that can find a generalization to various physical systems.…”
Section: Introductionmentioning
confidence: 99%